2000
DOI: 10.1007/bf02707394
|View full text |Cite
|
Sign up to set email alerts
|

Exchange rates and European countries’ export prices: An empirical test for asymmetries in pricing to market behavior

Abstract: F12, F14,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 16 publications
1
17
0
4
Order By: Relevance
“…This latter result is line with the market share explanation. It is important to note that similar mixed result was pointed out by a number of empirical studies (Gil-Pareja, 2000, andCoughlin andPollard, 2004). Next, we check the asymmetry of pass-through with respect exchange rate magnitude.…”
Section: Resultssupporting
confidence: 61%
See 3 more Smart Citations
“…This latter result is line with the market share explanation. It is important to note that similar mixed result was pointed out by a number of empirical studies (Gil-Pareja, 2000, andCoughlin andPollard, 2004). Next, we check the asymmetry of pass-through with respect exchange rate magnitude.…”
Section: Resultssupporting
confidence: 61%
“…Nevertheless, our findings corroborate with previous empirical studies which provide also no clear evidence on the direction of asymmetry in ERPT. For a set of European industries, Gil-Pareja (2000) found that the direction of the asymmetry varied across industries and countries. Coughlin and Pollard (2004) confirm the same results in their study on 30 U.S. industries.…”
Section: Results From Lstr Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…2 The literature on exchange rate pass-through, in turn, reports several sources of nonlinearity, indicating that the degree of pass-through can be related to some macroeconomic variable, including the exchange rate. Mann (1986), Goldberg (1995), Gil-Pareja (2000), Mahdavi (2002) and Olivei (2002) have found asymmetric pass-through related to the direction of exchange rate changes, while Ohno (1989) and Pollard and Coughlin (2004) have indicated the presence of asymmetry associated with the magnitude of exchange rate changes.…”
Section: Introductionmentioning
confidence: 99%